2020
DOI: 10.4317/medoral.23292
|View full text |Cite
|
Sign up to set email alerts
|

People would rather see a physician than a dentist when experiencing a long-standing oral ulceration. A population-based study in Spain

Abstract: Background Primary care physicians have been reported to be the first choice for patients with oral ulcerations. This study investigates the health-seeking behaviour of lay public in Galicia (North-western Spain) if experiencing a long-standing oral ulceration. Material and Methods Cross-sectional population-based survey of randomly selected respondents conducted from March 1, 2015 to 30 June 2016. Results A total of 5,727 pedestrians entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…18 Interestingly, patients preferred to see a medical doctor instead of a dentist when having a non-healing oral ulcer. 19 Unfortunately, this was a consistent finding in all our patients presented in this report. Despite this, medical practitioners do not include orofacial screening as a routine part of the patient's assessment.…”
Section: Discussionsupporting
confidence: 83%
“…18 Interestingly, patients preferred to see a medical doctor instead of a dentist when having a non-healing oral ulcer. 19 Unfortunately, this was a consistent finding in all our patients presented in this report. Despite this, medical practitioners do not include orofacial screening as a routine part of the patient's assessment.…”
Section: Discussionsupporting
confidence: 83%
“…However, we found that women with OSCC showed a better survival, and despite not being significant in our study, other authors have recognised this difference in prognosis ( 11 , 14 , 16 ). This observations could be related to a lower consumption of tobacco and/or alcohol, as well as the earlier diagnosis of OSCC in women, as suggested in other studies conducted in Galicia ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 64%
“…However, we found that women with OSCC showed a better survival, and despite not being significant in our study, other authors have recognised this difference in prognosis (11,14,16). This observations could be related to a lower consumption of tobacco and/or alcohol, as well as the earlier diagnosis of OSCC in women, as suggested in other studies conducted in Galicia (17,18). In Galicia, a large majority of patients with OSCC are regular consumers of tobacco and/or alcohol, which remains the most important known oral carcinogenic binomial, and whose consumption numbers have been similar to those in other studies (6,12).…”
Section: Discussionsupporting
confidence: 55%
“…The reasons patients chose a GP or a GDP for consultation when experiencing possible symptoms of oral cancer is not known, although financial reasons or tumour sites may have played a role [46]. A recent community-based study showed that patients with a persistent oral ulceration-the most frequent presenting symptom-preferred consultation with a GP [47]. In addition, the number of consultations before referral has been proposed as a subrogated indicator of the primary care interval [48], especially for "harder to suspect" cancers (multiple myeloma, or pancreatic or stomach carcinomas), which generate more consultations and longer primary care intervals [22,48].…”
Section: Prereferral Interval (Gp Vs Gdp)mentioning
confidence: 99%